SMART TOURISM AND VISITOR DECISION-MAKING: AN EMPIRICAL STUDY ON MOBILE APPLICATION USE AT MANGKUNEGARAN PALACE - Debora Shinta Dewi; Nining Yuniati; Moch Nur Syamsu; Agung Yuliyanto Nugroho (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the influence of smart tourism features in a mobile application on tourists’ decision to visit Pura Mangkunegaran Surakarta. Using a quantitative approach, the research tested four main smart tourism features: (1) Historical Information, (2) Cultural Gallery, (3) Cultural Events and News, and (4) Educational and Interactive Features. The study used a multiple linear regression method with data collected from 96 domestic respondents. The results show that all four smart tourism features simultaneously and partially have a significant effect on the decision to visit. The most influential features are Historical Information and Educational-Interactive content. These results emphasize the importance of digital platforms in promoting and preserving cultural tourism through smart technologies.